Laboratory Tests for the Diagnosis of Clostridium difficile - Carroll, Karen C.; Mizusawa, Masako (Clinics in Colon and Rectal Surgery, 2020)
Clostridium (reclassified as “Clostridioides”) difficile is an anaerobic, gram-positive bacterium that causes significant disease through elaboration of two potent toxins in patients whose normal gut microbiota has been altered through antimicrobial or chemotherapeutic agents (dysbiosis). The optimum method of laboratory diagnosis is still somewhat controversial. Recent practice guidelines published by professional societies recommend a two-step approach beginning with a test for glutamate dehydrogenase (GDH), followed by a toxin test and/or a nucleic acid test. Alternatively, in institutions where established clinical algorithms guide testing, a nucleic acid test alone is acceptable. Nucleic acid tests are the methods of choice in approximately 50% of laboratories in the United States. These tests are considered as the most sensitive methods for detection of C. difficile in stool and are the least specific. Because of the lower specificity with nucleic acid tests, some clinicians believe that toxin enzyme immunoassays are better predictors of disease, despite their known poor performance in certain patient populations. This review will discuss the advantages and disadvantages of the currently available test methods for the diagnosis of C. difficile with a brief mention of some novel assays that are currently in clinical trials.
Keywords: Clostridium difficile; diagnosis; toxins; diarrhea; enzyme immunoassay; nucleic acid tests; toxigenic culture; cytotoxicity